Refunctionalising the Past: Salman Rushdie’s Re-Writing of the Eighteenth-Century Novelistic Conventions in Midnight’s Children - de Juan Hatchard, Luis (Miscelánea: A Journal of English and American Studies, 1992)
Salman Rushdie’s novel Midnight’s Children consciously “works” with the conventions used by eighteenth-century writers of fictional autobiographies, such as Defoe, giving them new life and a parodic function. The attempt to undermine a coherent, stable view of the self and of society is paralleled by the attempt to undermine the conventions which the literary works belonging to that culture are based upon. In this way, Rushdie has superbly shown how the heavy burden of tradition can be used to the writer’s own benefit.